Fog harvesting: A sustainable design and material analysis (2024)
Fog harvesting offers a sustainable solution to the pressing issue of water shortages. This method involves a vertically oriented mesh positioned perpendicular to the incoming fog, which allows fog to condense on its surface. The condensed droplets then flow down to a gutter or water-collection system, providing a source of drinking water. Given the acute water scarcity, especially in rural communities situated in mountainous or arid regions, this project aims to investigate and design an economically, environmentally, and socially sustainable system capable of collecting 3.7 liters of water per day. To achieve this objective, the project experimented with the harp mesh mechanism, utilizing materials with varying thermal conductivities to analyze the mesh efficiency when changing the heat transfer rate. A fog simulation device was designed, along with scaled-down meshes created using 3D printing for the frames. The investigation demonstrated that all the tested materials were capable of collecting the same amount of water. When scaled up to a 1-meter by 1-meter mesh, these materials can each collect 3.7 liters of water in a fog-like environment.